1999
DOI: 10.1007/s002800051123
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin inhibits the growth of mammary tumors despite the existence of a novel wortmannin-insensitive phosphatidylinositol-3-kinase

Abstract: The results of the current study demonstrate that wortmannin can inhibit the growth of murine and human mammary tumors despite the presence of novel wortmannin-insensitive PtdIns 3-kinases in these tissues suggesting that some other target is responsible for wortmannin's antitumor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In addition to this, Schultz et al [25] demonstrated inhibition of PI3K activity by wortmannin to inhibit growth of the murine C3H mammary carcinoma and the human BxPC3 pancreatic tumor in a xenograft model. These findings were reproduced by Lemke et al [17] in murine MCF-7 and C3H mammary tumors. However, according to Schultz et al [25], the ability of wortmannin to inhibit C3H tumor growth is not related to inhibition of tumor PI3K activity, suggesting an additional site of action for wortmannin to inhibit tumor growth.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to this, Schultz et al [25] demonstrated inhibition of PI3K activity by wortmannin to inhibit growth of the murine C3H mammary carcinoma and the human BxPC3 pancreatic tumor in a xenograft model. These findings were reproduced by Lemke et al [17] in murine MCF-7 and C3H mammary tumors. However, according to Schultz et al [25], the ability of wortmannin to inhibit C3H tumor growth is not related to inhibition of tumor PI3K activity, suggesting an additional site of action for wortmannin to inhibit tumor growth.…”
Section: Discussionsupporting
confidence: 83%
“…PI3K has been identified as a potential target for anticancer drug development because of its role as a component of growth factor and oncogene activated signaling pathways [14]. Wortmannin (C 23 H 24 0 8 ), a highly cell permeable fungal metabolite from Penicillium fumiculosum, acts as a selective, irreversible inhibitor of the catalytic p110 PI3K subunit [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…PI 3-K inhibitors such as wortmannin and LY294002 are known to possess anti-tumor activities (30,31) and previous studies have indicated that the PI 3-K/Akt signaling pathway can modulate TRAIL-mediated apoptosis in cancer cells (22)(23)(24)32,33). Therefore, we used HSC-2 and NA cell lines, which are resistant to TRAIL-induced apoptosis, to examine the effect of treatment with PI 3-K inhibitors on susceptibility to apoptosis via this process.…”
Section: Discussionmentioning
confidence: 99%
“…38 Several studies have reported that wortmannin has an antitumor effect in human breast cancer cell lines, and are inconsequential in the MCF-7 context, specifically from the programmed cell death perspective. [39][40][41][42][43] To the best of our knowledge, there are no further reports on the details of the mechanism of action on MCF-7 cell death. Therefore, we have explored for the first time the possible mechanism of cell death induced by wortmannin in MCF-7 cells by focusing on its ability to induce programmed cell death.…”
Section: Discussionmentioning
confidence: 99%